Open surgery versus TEVAR in complicated type B acute aortic syndromes: outcomes of a single referral center. (25th November 2020) - Botta, L; Gliozzi, G; Di Marco, L; Leone, A; Amodio, C; Berardi, M; Coppola, G; Pagliaro, M; Loforte, A; Murana, G; Savini, C; Lovato, L; et al.
Abstract: Background: While patients with uncomplicated acute Type B aortic syndromes (ATBAS) are usually managed with optimal medical therapy, complicated ATBAS require a quick intervention to prevent life-threatening complications. If anatomical features are favorable, TEVAR is the preferred treatment option. Nevertheless, open surgery still plays a significant role in selected cases. The optimal approach to complicated ATBAS remains matter of debate. Purpose: We retrospectively evaluated our seventeen-years' experience as regional referral center for acute aortic syndromes to analyze the outcomes of TEVAR and open surgery in cases of complicated ATBAS. Methods: Between January 2000 and December 2016, 199 patients with ATBAS were referred to our hospital: 133 aortic dissections, 53 intramural hematomas, 13 penetrating ulcers. All patients were evaluated by a multidisciplinary aortic team. 113 patients (56.8%) received the optimal medical therapy being uncomplicated, while 86 (43.2%) patients admitted with or developing a complicated form of ATBAS underwent TEVAR or open surgery during the same hospital admission. Open surgical repair was performed in cases of unsuitable anatomy for TEVAR, retrograde involvement of the arch, ascending aorta ectasia or aneurysm. In-hospital outcomes, long term survival and freedom from reoperation were analyzed and compared between the groups. Results: No differences were observed in terms of in-hospital mortality between uncomplicated and complicated ATBAS (13.3% versus 14.0% respectively [p=0.890]). Complicated ATBAS were treated for unstable anatomical evolution (34 patients), refractory pain or uncontrollable hypertension (19 patients), visceral or peripheral malperfusion (18 patients) or impending rupture in 15 patients. Sixty-eight patients (79%) underwent TEVAR while 18 underwent open surgery (16 frozen elephant trunk [FET] and 2 descending thoracic aorta replacement). Operative timing from the onset of symptoms did not differ between two groups (9+10 (TEVAR) versus 14+16 (Open) days [p=0.233]). In-hospital mortality was 13.2% in TEVAR group versus 16.7% in open surgery (p=0.709). Postoperative myocardial infarction, visceral and peripheral ischemia and neurological outcomes were similar in two groups (p>0.05), but acute kidney injury was higher in open surgery cohort (p=0.027). One, 5 and 10-years survival of uncomplicated ATBAS (medical therapy) were 75%, 58%, 34% vs. 76%, 65%, 58% in TEVAR and 83%, 76%, 76% in open surgery groups (Log rank p=0.329). Comparing TEVAR and open surgery, freedom from endovascular reoperation at 1 and 5 years was 86%, 78% vs. 66%, 60% respectively (Log rank p=0.091). Conclusions: Surgical treatment options (open and TEVAR) modify the natural history of complicated acute type B aortic syndromes. Open surgery represents a good option in selected cases with in-hospital and long-term survival at least comparable to TEVAR. Funding Acknowledgement: Type of funding source: None